Evaluating barriers to effective rural stakeholder engagement in catchment management in Malawi - Chunga, Brighton A.; Graves, Anil; Knox, Jerry W. (Elsevier, 2023)
Water quality and quantity are heavily influenced by catchment management, yet without participation by local communities, opportunities for enhanced protection and conservation in rural areas is limited. This paper explores the factors hindering local participation in catchment management, analysing stakeholder engagement by conducting in-depth interviews, focus group discussions and evidence syntheses in three contrasting catchments in Malawi. Our findings reveal omission of key actors in the catchment management process. Rural communities were least involved in catchment management. Barriers limiting participation were found to be interlinked and complex including weak regulatory frameworks, inadequate resources, lack of commitment, corruption, resistance to change, poor coordination, and cultural factors. Analysis of the interlinkages highlighted areas for intervention in promoting stakeholder participation which would, in turn, improve water security at catchment level. A comprehensive theory of change-based engagement framework that considers specific socio-cultural, economic, and political contexts to overcome the identified barriers is proposed.
Keywords: Governance; Integrated water resources management; Water policy